2011
DOI: 10.1016/j.jsv.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The decoupling of defective linear dynamical systems in free motion

Abstract: a b s t r a c tIt was demonstrated in two earlier papers that there exists a real, linear, time-varying transformation that decouples any non-defective linear dynamical system in free vibration in the configuration space. As an extension of this work, the present paper represents the first systematic effort to decouple defective systems. It is shown that the decoupling of defective systems is a rather delicate procedure that depends on the multiplicities of the system eigenvalues. While any defective system ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…This system possesses at least one real, defective eigenvalue. Decoupling of the system by phase synchronization confirms that one of the decoupled degrees of freedom is critically damped, which implies that one eigenvalue is real and defective [17]. The other degree of freedom is overdamped with viscous damping ratio 3.24.…”
Section: Examplementioning
confidence: 73%
See 4 more Smart Citations
“…This system possesses at least one real, defective eigenvalue. Decoupling of the system by phase synchronization confirms that one of the decoupled degrees of freedom is critically damped, which implies that one eigenvalue is real and defective [17]. The other degree of freedom is overdamped with viscous damping ratio 3.24.…”
Section: Examplementioning
confidence: 73%
“…It follows that system (1) generally cannot be decoupled into a set of mutually independent, real, scalar, second-order equations by a linear mapping q(t) → Lp(t), with the linear operator L independent of t. However, it was recently shown that any system can be decoupled if one utilizes time-dependent transformations [17,20,21,23]. Here, we follow [23] closely to review how system (1) is decoupled.…”
mentioning
confidence: 99%
See 3 more Smart Citations